Four-stroke, internal combustion engine performance modeling - Wagner, Richard C., author; Kirkpatrick, Allan, advisor; Gao, Xinfeng, committee member; Robinson, R. Steve, committee member (Colorado State University. Libraries, 2017)
In this thesis, two models of four-stroke, internal combustion engines are created and compared. The first model predicts the intake and exhaust processes using isentropic flow equations augmented by discharge coefficients. The second model predicts the intake and exhaust processes using a compressible, time-accurate, Quasi-One-Dimensional (Q1D) approach. Both models employ the same heat release and reduced-order modeling of the cylinder charge. Both include friction and cylinder loss models so that the predicted performance values can be compared to measurements. The results indicate that the isentropic-based model neglects important fluid mechanics and returns inaccurate results. The Q1D flow model, combined with the reduced-order model of the cylinder charge, is able to capture the dominant intake and exhaust fluid mechanics and produces results that compare well with measurement. Fluid friction, convective heat transfer, piston ring and skirt friction and temperature-varying specific heats in the working fluids are all shown to be significant factors in engine performance predictions. Charge blowby is shown to play a lesser role.
Keywords: exhaust; intake; performance; flows; engine; modeling